Cuerpo, pedagogía y disciplina escolar en Cuba: dispositivos de control desde los discursos higienistas (1899-1958) - Cordoví Núñez, Joel (Revista de historia., 2012)
This article seeks to establish the contributions of speeches hygienists to treat school behaviors among years between the formalization of the first U.S. military occupation in 1899, and the triumph of the Cuban revolution in 1959. The structure responds to the delimitation assumed contextual three rationales for the treatment of conduct school teaching from the references provided by science hygienist in their different types: physical health, hygiene physiological and mental health.